<Perception of professional competence of Brazilian college coaches> - Ema Maria Egerland; William das Neves Salles; Marcelo Figueiró Baldi (Universidade Federal de Santa Catarina, 2014)
The aim of this study was to analyze the perceived level of professional competence of Brazilian college coaches, considering the type of sports discipline and professional development cycles. The target population consisted of 92 sport coaches of both genders from various regions of Brazil, who worked in team or individual sports. An adapted version of the Self-Perception of Competence Scale was used for data collection. Statistical analysis was performed by Chi-squared and Fisher's exact tests, adopting a level of significance of 5%. The coaches perceived themselves as competent in knowledge on the theory and methodology of sports training and sports biodynamics, as well as in the skills of sports planning and management. On the other hand, the coaches perceived fragility of knowledge on sports management and legislation. With respect to professional development cycles, more experienced coaches perceived themselves as more competent than those with a shorter coaching experience. When coaches of individual and team sports were compared, a significant difference (p = 0.04) was only observed for knowledge on sports management and legislation, with coaches of team sports perceiving themselves as more competent. Further studies are needed to improve the basic and continuing education of Brazilian sport coaches, as well as to obtain a better understanding of the relationship between career development and the acquisition of professional skills.